Are antipsychotic drugs the right treatment for challenging behaviour in learning disability?: The place of a randomised trial. Issue 5 (1st October 2001) - Ashcroft, Richard; Fraser, Bill; Kerr, Michael; Ahmed, Zahir
Abstract : People with learning disability sometimes display challenging behaviour. This can be managed by use of antipsychotic medication or behavioural therapy or both. There is no solid evidence, however, that these therapies are safe and effective. A randomised controlled trial of antipsychotic medication has been proposed to deliver such evidence. However, this presents difficult issues in the ethics of research with learning disabled people. In particular, is a trial the most efficient and fairest way to evaluate practice in this area? This paper reviews the clinical situation, gives the rationale for the trial, and analyses the ethical arguments for and against such a trial.